PENGGUNAAN STRATEGI GRADASI WARNA DALAM MENINGKATKAN KREATIVITAS ANAK DI TAMAN KANAK KANAK - Erisna; Nurhafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creativity is crucial for early childhood. However, many kindergarten children still struggle to express their ideas. This study aims to enhance children's creativity through a color gradation strategy. The method used was Classroom Action Research (CAR) in two cycles. The subjects were children in Group B at Jihad Kindergarten. Data were collected through observations of coloring activities and documentation of children's work. Before the action, children's creativity was at 20%. After the action, the percentage of children completing the coloring activity increased to 40%. Because it had not yet reached the minimum completion percentage, it was continued to Cycle II. In Cycle II, children's completion increased significantly, reaching 80%. In conclusion, the color gradation strategy has proven effective in significantly increasing the creativity of kindergarten children. Keywords: Color Gradation Strategy, Children's Creativity, Kindergarten.